Korelasi Faktor yang Berhubungan dengan Kejadian Pneumonia Balita di Dua Puskesmas Kota Jambi - Armina Armina; Arnati Wulansari (Universitas Batanghari Jambi, 2020)
The prevalence of pneumonia in infants in Jambi province has increased the last few years, especially the city of Jambi in 2015 by 44.14%. Pneumonia is also widely recorded in the health center of Jambi. The purpose of this research is to identify factors that correlate with the incidence of infant pneumonia in two centers of Jambi City. The research was conducted at the site of Tahtul Yaman and Kebon Handil Puskesmas working area with the design of case control correlation. Sampling technique with purposive sampling amount of 55 (case) and 55 (control). Test the analysis using Chi Square and logistic regression. The Chi Square test is derived that the exclusive ASI-history factor, ISPA history, Mother's education, treatment history and environment has a significant relationship with the incidence of infant pneumonia (P value < 0.05). The test results of a logistic regression model found that the most correlated factor of Pneumona is the exclusive ASI-history, ISPA history, and treatment history. Researchers expect an effort to raise the awareness of mothers on prevention of infant pneumonia.